Clinical Innovation: A Multidisciplinary Program for the Diagnosis and Treatment of Systemic Hypertension in Children and Adolescents. (March 2020) - Kaplinski, Michelle; Griffis, Heather; Liu, Fang; Tinker, Craig; Laney, Nina C.; Mendoza, Melodee; Cohen, Meryl S.; Meyers, Kevin; Natarajan, Shobha S.
Pediatric systemic hypertension (HTN) is underdiagnosed and undertreated. The Divisions of Cardiology and Nephrology at our institution developed a comprehensive outpatient HTN program to (1) screen children at risk for HTN, (2) assess cardiovascular health, and (3) optimize medical management. We report our findings during all initial visits (n = 304) from December 2011 to September 2018. Of the cohort, 38% were obese and 36% reported little to no exercise. More than half of patients ≥11 years old did not have recommended lipid screening. When evaluating ambulatory blood pressure monitoring results, clinic blood pressure did not accurately diagnose patients with or without HTN and many patients on antihypertensive medications were inadequately treated. Visit recommendations included addition of or changes to antihypertensive medication in 35% of patients. A multidisciplinary program dedicated to pediatric HTN helps screen patients who are at risk. Ambulatory blood pressure monitoring identifies HTN in patients with normal clinic blood pressure and those on antihypertensive medication.